Poluição por fragmentos plásticos flutuantes: abundância, composição e distribuição espacial do séston ao longo da ecoclina estuarina de uma lagoa costeira subtropical - Monteiro, Isabel Boaventura (2021)
Studies on the spatial patterns of seston in estuarine environments are of great importance to understand how the available resources are used, as well as how anthropic action can negatively interfere with them. In the present study, estuarine seston is represented by zooplankton, ichthyoplankton (fish eggs and larvae) and floating plastic fragments, which undergo constant changes due to the estuarine environmental gradient, influenced by gradual changes in local abiotic variables. Studies on zooplankton and ichthyoplankton communities and plastic fragments are necessary for the Santo Antônio dos Anjos lagoon (Laguna/SC), an environment of great ecological and socioeconomic importance in the region, which has suffered great environmental impacts. In this region, no study has been done to collect data about these communities and their pollutant sources. Therefore, the objective of this study was to characterize the composition and spatial distribution of seston along the estuarine ecocline of the Santo Antônio dos Anjos lagoon. In the months of September and November 2016, sampling was carried out in 5 different areas of the Santo Antônio dos Anjos lagoon (3 replicates per area): A1 (Coastal waters), A2 (Bar channel), A3 (Lower Tubarão River), A4 (Central area of the lagoon) and A5 (Internal area of the lagoon). This study emerges as an initiative to describe the distribution and interaction of these three components of the local estuarine environment, generating important information for future environmental management processes.